2006
DOI: 10.1265/ehpm.11.313
|View full text |Cite
|
Sign up to set email alerts
|

Practicality of Veterans Specific Activity Questionnaire in Evaluation of Exercise Capacity of Community-Dwelling Japanese Elderly

Abstract: Objective: The aim of this study is to determine whether a questionnaire-based method using the Veterans Specific Activity Questionnaire (VSAQ) is a practical tool for the development of a safe exercise program to prevent a reduction in physical performance.Methods: One hundred and twenty-one senior residents of Yakage, Okayama, agreed to voluntarily participate in this study. They were asked to complete a questionnaire for information on age, sex, subjective health status, exercise habits and VSAQ. We investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…As in the original protocol13 and subsequent validations,14–17 the following formula was used to provide a score of predicted METs or exercise capacity based on the VSAQ score and the participant’s age:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the original protocol13 and subsequent validations,14–17 the following formula was used to provide a score of predicted METs or exercise capacity based on the VSAQ score and the participant’s age:…”
Section: Methodsmentioning
confidence: 99%
“…One MET is equal to the consumption of 3.5 mL O 2 per kilogram of body weight per minute. In the general population, numerous studies have validated the use of the VSAQ in the evaluation of exercise capacity, and have shown good correlation with CPET indices14–16 and mortality 17…”
Section: Introductionmentioning
confidence: 99%
“…In other previous studies on middle-aged and elderly persons (Lamb, 1992;Nishijima et al, 1993;Kinugasa & Nagasaki, 1998;Nishijima et al, 2003), it has been reported that the questionnaire-using physical fitness estimation method correlated at about rϭ0.4-0.6 with the physical performance test and so was valid. Kojima et al (2006) found that physical fitness estimated by a questionnaire correlated significantly with the score for the 6-min walk at rϭ0.56 in elderly people ( pϽ0.001), and suggested that exercise intensity can be set within safe limits appropriate for individuals. It was suggested that the proposed CAT-using physical fitness estimation method, which was comparable to or exceeded previous studies in terms of the validity, can be utilized adequately for estimating physical fitness.…”
Section: Validity and Application Of Cat-using Physical Fitness Estimmentioning
confidence: 95%
“…Previously, relationships have been observed between questionnaire-using physical fitness estimation methods and physical performance tests; especially, Kojima et al (2006) suggested that exercise intensity can be set individually by a questionnaire-using physical fitness estimation method intended for elderly people. However, physical fitness estimation methods using a self-completed questionnaire impose a heavy burden on examiners and furthermore require much time, for the series of tasks consisting of collection, aggregation, and analysis of the questionnaire.…”
mentioning
confidence: 99%
“…The 6MD test was conducted on a 30-m long, hard, flat indoor corridor marked with orange traffic cones every 3 m. 6MD results are highly correlated with maximum oxygen uptake [21] and indicate the distance (m) that a person can cover in 6 min while walking quickly on a flat surface. This test imposes a decreased burden on a subject and easily evaluates ADL [22]. 6MD was recorded for all patients before and 1 month after the intervention.…”
Section: Six-min Walking Distance (6md)mentioning
confidence: 99%